MRI in Kernicterus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The magnetic resonance images (MRI) of three children with athetotic cerebral palsy and severe neonatal jaundice were examined in the Department of Pediatric Neurology, Ohzora-no-iye Hospital and Seirei-Mikatahara General Hospital, Shizuoka, Japan.